2022
DOI: 10.18196/jesp.v23i2.14881
|View full text |Cite
|
Sign up to set email alerts
|

Does Monetary Policy Respond to Macroeconomic Shocks? Evidence from Indonesia

Abstract: The activist policy is believed by policymakers and economists that monetary policy can respond to macroeconomic shocks to stabilize the economy. This study aims to find evidence and discuss the response of monetary policy to macroeconomic shocks. For this reason, the effects of GDP shocks, inflation shocks, and exchange rate shocks on policy interest rates in the implementation of monetary policy are discussed through vector error correction model (VECM) analysis along with policy interest rate responses invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…Raising interest rates has increased the demand for the rupiah and appreciated its exchange rate. This finding supports the study conducted by Arintoko and Kadarwati (2022) in the case of Indonesia, Fang and Zhang (2021) in the case of RMB China, and Garg and Prabheesh (2021) in a case of Brazil, Russia, India, China, and South Africa (BRICS countries) and also Pham (2019) in case of Vietnam. Bank Indonesia's 7-days (reverse) repo rate as a proxy of the central bank interest rate has the highest effect compared to other explanatory variables used in this study in maintaining the rupiah exchange rate.…”
Section: Resultssupporting
confidence: 90%
“…Raising interest rates has increased the demand for the rupiah and appreciated its exchange rate. This finding supports the study conducted by Arintoko and Kadarwati (2022) in the case of Indonesia, Fang and Zhang (2021) in the case of RMB China, and Garg and Prabheesh (2021) in a case of Brazil, Russia, India, China, and South Africa (BRICS countries) and also Pham (2019) in case of Vietnam. Bank Indonesia's 7-days (reverse) repo rate as a proxy of the central bank interest rate has the highest effect compared to other explanatory variables used in this study in maintaining the rupiah exchange rate.…”
Section: Resultssupporting
confidence: 90%
“…Despite its use as a countercyclical tool to stimulate economic growth, monetary policy can also lead to an increase in prices due to an increase in money supply. This outcome is consistent with the findings of previous studies (Arintoko & Kadarwati, 2022;Nyumuah, 2018;Abbasinejad et al, 2018;Sethi et al, 2019;Mandel et al, 2019;Arintoko, 2021;Tai Nguyen et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…The results differ from those of (Paksi, 2021), who states that the interest rate has no significant impact on economic growth. (Arintoko & Kadarwati, 2022) Show that interest rates respond positively to unexpected GDP changes. There are different results for the interest rate and inflation because the interest rate is a government tool to control higher inflation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interest rate is one variable affecting inflation (Kurniawan et al, 2022). The interest rate is one of the main instruments for monetary policy conducted by central banks (Arintoko & Kadarwati, 2022;Johari et al, 2022). Sulistiana et al (2017) found that the interest rate, proxied by the BI rate (interest rate targeted by the Indonesian central bank), is the most dominant factor that affects inflation.…”
Section: Introductionmentioning
confidence: 99%